A qualitative research analysis of post secondary academic adventure education organizations' World Wide Web home pages - Gould, Michael D., author; Banning, James H., advisor; Feller, Richard, advisor; Kees, Nathalie, committee member; Hartman, Jackie L., committee member (Colorado State University. Libraries, 2003)
Whereas organizational culture traditionally has been associated with members affiliated with an organization, the World Wide Web (WWW) projects cultural information internationally to individuals with Internet access to an organization's web site. WWW sites may be understood as omnipresent cultural symbols that are potentially available to web users on an "any time" world wide basis. As a cultural artifact, the WWW has the potential to inform and influence organizational web page cultural participants. The goal of this qualitative research was to evaluate WWW home pages from a multimedia / multi-disciplinary perspective. Print publications and WWW home pages were the 2 mediums reviewed to research organizational program content and web page design disciplines. Using a basic interpretive inductive methodology, 25 post-secondary adventure education (AE) home pages, 5 AE publications, and 9 WWW page design publications were reviewed to identify and evaluate emergent cultural themes. The research objective in the first phase was to identify and describe cultural themes from (a) AE publication program content (b) AE home page program content (c) AE web page technical design and (d) WWW publication web page design literature. The purpose of the second and third phases was to evaluate the similarities among the AE home pages based on inclusion of the multimedia and multi-discipline cultural themes. The results of the research indicated that there were numerous dissimilarities among the AE home page cultural themes, the AE publications program content themes and the WWW page publication design themes. Group activity was the only program content culture theme found in both mediums and the text-background contrast theme was the only similar theme for web page design. Based on the findings of this research, the cultural messages projected on the 25 adventure education organizations' WWW home pages may cause communication conflict for potential participants. Incorrect messages may negatively influence viewer's interpretation of acceptable organizational behavior. To project a consistent organizational culture, adventure education web pages should be based on professional standards and integrated with other internal and external communication mediums.
Keywords: mass media; recreation; mass communications; information science